Tracheal Occlusion Conditioning in Conscious Rats Modulates Gene Expression Profile of Medial Thalamus - Bernhardt, Vipa; Hotchkiss, Mark T.; Garcia-Reyero, Natàlia; Escalon, Barbara L.; Denslow, Nancy; Davenport, Paul W. (Frontiers in Physiology, 2011)
The thalamus may be the critical brain area involved in sensory gating and the relay of respiratory mechanical information to the cerebral cortex for the conscious awareness of breathing. We hypothesized that respiratory mechanical stimuli in the form of tracheal occlusions would modulate the gene expression profile of the thalamus. Specifically, it was reasoned that conditioning to the respiratory loading would induce a state change in the medial thalamus consistent with a change in sensory gating and the activation of molecular pathways associated with learning and memory. In addition, respiratory loading is stressful and thus should elicit changes in gene expressions related to stress, anxiety, and depression. Rats were instrumented with inflatable tracheal cuffs. Following surgical recovery, they underwent ten days (5 days/week) of transient tracheal occlusion conditioning. On day 10, the animals were sacrificed and the brains removed. The medial thalamus was dissected and microarray analysis of gene expression performed. Tracheal obstruction conditioning modulated a total of 661 genes (p < 0.05, log2 fold change ≥ 0.58), 250 genes were down-regulated and 411 up-regulated. There was a significant down-regulation of GAD1, GAD2 and HTR1A, HTR2A genes. CCK, PRKCG, mGluR4, and KCJN9 genes were significantly up-regulated. Some of these genes have been associated with anxiety and depression, while others have been shown to play a role in switching between tonic and burst firing modes in the thalamus and thus may be involved in gating of the respiratory stimuli. Furthermore, gene ontology and pathway analysis showed a significant modulation of learning and memory pathways. These results support the hypothesis that the medial thalamus is involved in the respiratory sensory neural pathway due to the state change of its gene expression profile following repeated tracheal occlusions.